2023
DOI: 10.1101/2023.03.19.532758
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diverse and abundant phages exploit conjugative plasmids

Abstract: Viruses exert profound evolutionary pressure on bacteria by interacting with receptors on the cell surface to initiate infection. While the majority of bacterial viruses, phages, use chromosomally-encoded cell surface structures as receptors, plasmid dependent-phages exploit plasmid-encoded conjugation proteins, making their host range dependent on horizontal transfer of the plasmid. Despite their unique biology and biotechnological significance, only a small number of plasmid-dependent phages have been charac… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 104 publications
(129 reference statements)
0
4
0
Order By: Relevance
“…Consequently, CRISPR-Cas may not always be essential but moderately beneficial for bacterial survival and therefore it could be located on a plasmid. Second, phages that depend on plasmids for infection are more abundant than previously thought [ 39 ]. These phages can only infect bacterial cells hosting a plasmid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, CRISPR-Cas may not always be essential but moderately beneficial for bacterial survival and therefore it could be located on a plasmid. Second, phages that depend on plasmids for infection are more abundant than previously thought [ 39 ]. These phages can only infect bacterial cells hosting a plasmid.…”
Section: Discussionmentioning
confidence: 99%
“…R. Soc. B 291: 20232449 mobile genetic elements to estimate the consequences of their interactions for bacterial ecology and evolution, contributing to the recent attention in understanding the multi-party interactions between mobile genetic elements [6,10,[38][39][40].…”
Section: (B) Plasmid Segregation Loss Favours Phage Survival By Facil...mentioning
confidence: 99%
“…Interestingly, a significant proportion of type IV CRISPR spacers match plasmid conjugation genes 7 , which are also involved in pilus formation. For example, phages using pili as receptors are widespread 53 , and it is possible that type IV-driven pili repression enhances plasmid fitness by preventing phage entry into host cells.…”
Section: Discussionmentioning
confidence: 99%
“…Even so, the knowledge of these phages is limited, although some recent studies have shown that some of them can have a great potential to be used to reduce ARGs’ load in microbial communities ( 22 24 ). Recently, He et al ( 25 ) and Quinones-Olvera et al ( 26 ) demonstrated that plasmid-dependent phages are in fact common and abundant in diverse environments.…”
Section: Introductionmentioning
confidence: 99%